INNOVATION OF POPULATION ADMINISTRATION SERVICES THROUGH THE SI SUPERLARIS APPLICATION - Al Qaddafi, Yngwie Herfi; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study was designed with the aim of analyzing the process of diffusion of innovation in population administration services through the Si Superlaris application in Tulangan District, Sidoarjo, using the innovation diffusion theory of Everett M. Rogers and Floyd Shoemaker. This innovation comes in response to the need for more orderly and faster death registration to avoid social conflicts related to inheritance rights. Method: This research uses a qualitative research paradigm that is descriptive, with a data collection framework that includes three main techniques, namely interviews, observations, and documentation. Results: The results of the study show that the Si Superlaris application is able to simplify the procedure for submitting an heir's statement letter online by validating documents through a barcode signature. The implementation of this innovation has proven to be effective from four main indicators: ease of innovation, stable use period, support of social systems, and open communication between stakeholders. The original contribution of this research lies in the application of a holistic approach in examining technological innovations in population services at the sub-district level that has not been explored before. Novelty: This application is considered to be able to improve bureaucratic efficiency, ensure document legality, and strengthen digital governance that is transparent and responsive to the needs of the community.